Riverine photosynthesis influences the carbon sequestration potential of enhanced rock weathering - Neumann, Rebecca B.; Kukla, Tyler; Zhang, Shuang; Butman, David E. (Frontiers in Climate, 2025)
As climate mitigation efforts lag, dependence on anthropogenic CO2 removal increases. Enhanced rock weathering (ERW) is a rapidly growing CO2 removal approach. In terrestrial ERW, crushed rocks are spread on land where they react with CO2 and water, forming dissolved inorganic carbon (DIC) and alkalinity. For long-term sequestration, these products must travel through rivers to oceans, where carbon remains stored for over 10,000 years. Carbon and alkalinity can be lost during river transport, reducing ERW efficacy. However, the ability of biological processes, such as aquatic photosynthesis, to affect the fate of DIC and alkalinity within rivers has been overlooked. Our analysis indicates that within a stream-order segment, aquatic photosynthesis uptakes 1%–30% of DIC delivered by flow for most locations. The effect of this uptake on ERW efficacy, however, depends on the cell-membrane transport mechanism and the fate of photosynthetic carbon. Different pathways can decrease just DIC, DIC and alkalinity, or just alkalinity, and the relative importance of each is unknown. Further, data show that expected river chemistry changes from ERW may stimulate photosynthesis, amplifying the importance of these biological processes. We argue that estimating ERW’s carbon sequestration potential requires consideration and better understanding of biological processes in rivers.